10.2k views
20 votes
Help ASAP plz ASAP please

Help ASAP plz ASAP please-example-1
User Nohayeye
by
5.1k points

2 Answers

6 votes

Answer:

y = 6

Explanation:


(3y)/(2) -1 =8


(3y)/(2) -1 + 1 =8 +1


(3y)/(2) = 9


(3y)/(2) × 2 = 9 × 2

3y = 18

3y/3 = 18/3

y = 6

Double check:


(3(6))/(2) - 1 = 8


(18)/(2) -1 =8

9 - 1 = 8

8 = 8

User Phoxd
by
5.4k points
4 votes

Answer:

y = 6

Explanation:

3y/2 - 1 = 8

3y/2 = 8 + 1

3y/2 = 9

3y = 9 × 2

3y = 18

y = 18/3

y = 6

User Sajib Mahmood
by
6.1k points